Indoor Localization and Path Planning of Mobile Disinfection and Epidemic Prevention Robot - Su, Wei; Qin, Tao; Wang, Jia; Wen, Jingyang (Recent Patents on Mechanical Engineering, 2025)
Introduction In response to the challenge of autonomous localization and navigation for mobile disinfection robots in unknown environments during the COVID-19 pandemic based on the existing patent technology of mobile robots, a localization and navigation approach combining the Cartographer-Simultaneous Localization and Mapping (SLAM) algorithm, an improved A* algorithm, and the Dynamic Window Approach (DWA) has been proposed, enabling effective disinfection and prevention work. Methods First, a comprehensive analysis of two laser SLAM algorithm frameworks, Gmapping-SLAM and Cartographer-SLAM, was conducted, which determined the Cartographer algorithm as the optimal SLAM algorithm for the mobile disinfection robot due to its superior performance. Second, an improved A* algorithm was developed based on its principles and integrated with the DWA algorithm for optimal path planning. Results Simulation and prototype experiments demonstrated that the proposed approach effectively solved the autonomous localization and navigation challenges faced by mobile disinfection robots in unknown environments, enabling successful disinfection and prevention tasks. Conclusion The proposed approach has the potential to lead to new patent applications in this field.
Keywords: A* algorithm